Gambaran Budaya Masyarakat Cina Dalam Sajak : Satu Analisis Teori Relevans - Liaw, Monica Kah Pei (Universiti Malaysia Sarawak, (UNIMAS), 2017)
This study is an empirical and qualitative study that focused on the identification of the Chinese culture in Malay poems by applying Relevance Theory pioneered by Sperber and Wilson (1986). In this study, 25 poems written by Lim Swee Tin and other related informations were obtained from four corpora which were further supported with reviews obtained from the library and interviews with the author. In order to identify these implicit Chinese cultures, five well known values and cultures in the Chinese community were observed with five poems for each values and cultures studied. Based on the findings of the study, the meanings and messages implied in those lines were detected with the theory applied. Apart from that, the implied meanings and messages have also found to be related and relevant with the values and cultures practised in the Chinese community. These findings therefore reflected that language is closely associated with cultures of a community. Not only that, the study also highlighted the importance of Relevance Theory in analysing the data as results obtained were more theoretical, academic and valid in terms of its validity. Thus, the results obtained were not only undisputed, but it is also an add-on to the existing facts and knowledge to the Malay and Chinese communities.